Analysis of a System Approach in Islamic Law Philosophy (Jasserauda's Perspective) - Muchamad Toif Chasani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Islam as a teaching can be studied from various perspectives. Both social, humanities, economic perspectives and even the legal perspective itself. This study will review Islam from a legal perspective as the main teaching of Islam. This study aims to describe JasserAuda's opinion about the purpose of the revelation of Islamic law by God seen from a systems philosophy approach. The research used in this paper is a literature review. Data were collected from various literary sources originating from JasserAuda's writings, namely The Philosophy As Islamic Law. Then the data were analyzed using content analysis. The results of this study indicate that the systems approach is carried out through several steps, namely: First, validating all knowledge. Second, using holistic principles. Third, courage is open and reforming. Fourth, determine the priority scale based on existing social conditions and not from the verbality of the text. Fifth, the multi-dimensional approach combined with the maqasid approach as a solution to the conflicting dilemma of two propositions. Sixth, taking maqasid as the determination of Islamic law.